INFLUENCE OF PHILOSOPHY ON ISLAMIC EDUCATION - Salwa Rahmadina; Siti Nurfadilah (Proceeding International Seminar of Islamic Studies, 2022)
This writing aims to find out what are the influences of philosophy on Islamic education. In line with the purpose of writing, the discussion of this article is: the nature of philosophy and Islamic education, the nature of philosophy islamic education, the principles and objectives of Islamic education, the role of teachers and the rights and obligations of students in Islamic education. The method used in writing this article is descriptive qualitative. The criteria for success are seen from the implementation of Islamic Education learning with the influence of Islamic philosophy. This can be seen from the way of thinking and understanding of educators and students towards the philosophy of Islamic education. It can be concluded that the influence of philosophy in Islamic education is as a knife of analysis on the problems of Islamic education, both theoretical and practical problems. Philosophy is the rationale that underlies and directs the implementation of Islamic Education learning activities.Keywords: Education, Islam, Influence, Philosophy____________________________________